Understanding Mechanistic Explanation as A Strategy of Analytical Sociology - Danjuma Sheidu Asaka; Olabode Awarun (CV. Literasi Indonesia, 2020)
Although Analytical Sociology is not often used in mainstream Sociology, its history is, however, traceable to the classical works of scholars such as Emile Durkheim, Max Weber, Alexis de Tocqueville as well as contemporary sociological thinkers like Talcott Parsons and Robert Merton, among others. This paper provides a contemporary argument for the application of mechanistic explanation in the overall understanding of Analytical Sociology using relevant and practical examples. In the course of this, attention has been paid to the concept of explanation and its various types in a sociological discourse. This paper therefore argues that social reality can significantly be understood only when explanations are systematic and detailed in content and context. The conclusion is that analytical sociology can explain the actions of social actors within the social environment beyond some social doubts, even though, not all situations, can be sufficiently explained with the strategy.